2011
DOI: 10.2174/1874917801104010102
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Harassment in the Workplace: Methods of Evaluation and Prevalence

Abstract: Abstract:Estimates of the prevalence of psychological harassment (mobbing/bullying) in the workplace vary enormously from one country to another. One of the main reasons for this variation is the method of evaluation used to make these estimates. Research on mobbing or bullying at work is basically guided by two methods: the perceived victimization method and the perceived exposure to bullying behaviors method. These methods, and their combination, were used to estimate the prevalence of bullying in a represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The studies within each continent also report a slight variation in the prevalence rates. The variation of prevalence rates within the continents might be due to the inconsistency in the use of measurement methods, tools and operational criteria (Baguena et al, 2011). This makes the comparison of prevalence rates within the continents very complex and difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies within each continent also report a slight variation in the prevalence rates. The variation of prevalence rates within the continents might be due to the inconsistency in the use of measurement methods, tools and operational criteria (Baguena et al, 2011). This makes the comparison of prevalence rates within the continents very complex and difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Using a self-reporting questionnaire, 10 per cent of the respondents were identified as victims of bullying; 39 per cent of the respondents reported to have observed bullying behaviours during the past six months. Baguena et al (2011) studied a representative sample of the working population in Spain ( N = 1,730). The measurement using Psychosocial Workplace Inventory with a definition revealed that 19.5 per cent of the sample self-labelled as victims of psychological harassment/bullying at various times in their work life.…”
Section: Prevalence Of Workplace Bullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…A key element of the definition of mobbing is that the individual exposed to the negative behaviours sees herself as a victim of these activities (Baguena, Belena, Toldos and Martinez, 2011).…”
Section: Defining and Measuring Mobbingmentioning
confidence: 99%
“…The research on mobbing uses various measurements which results in variation in results across but also within individual countries (Nielsen et al, 2010). This variation may also be attributed to inconsistency in the use of the measurement instruments (Baguena et al, 2011;Zapf et al, 2011). Two methods of quantitative measurement are most common.…”
Section: Defining and Measuring Mobbingmentioning
confidence: 99%